Digital Twin for rolling bearings: A review of current simulation and PHM techniques. (30th September 2022) - Peng, Fei; Zheng, Li; Peng, Yongdong; Fang, Congcong; Meng, Xianghui
Highlights: A first comprehensive overview of core contents of DT technology for rolling bearings is presented. The development history of DT is analyzed and the definition is clarified. Three core technologies of rolling bearings for the DT construction are reviewed. Challenges for the employment of these technologies in a rolling bearing DT system are discussed. Abstract: Digital Twin (DT) is acknowledged as a promising technology for life-cycle management of industrial products. Rolling bearings, the joints of machines, are largely responsible for the service performance and life of various high-end equipment. Up to now, there are still few investigations on rolling bearings under the concept of DT technology. The present paper reviews the brief history of DT technology and clarifies its definition. Then, the core technologies of rolling bearings for DT construction, including detection, modeling, and Prognostics Health Management (PHM) techniques are investigated through an extensive literature survey. Based on the above, this paper analyzes the challenges in the development of DT technology for rolling bearings and directions for future research.